2016
DOI: 10.1371/journal.pone.0157765
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Health Care Expenditure among Older People with Chronic Diseases in 15 European Countries

Abstract: IntroductionIt is well-known that the prevalence of chronic diseases is high among older people, especially those who are poor. Moreover, chronic diseases can result in catastrophic health expenditure. The relationship between chronic diseases and their financial burden on households is thus double-sided, as financial difficulties can give rise to, and result from, chronic diseases. Our aim was to examine the levels of catastrophic health expenditure imposed by private out-of-pocket payments among older people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 47 publications
(51 reference statements)
4
71
0
1
Order By: Relevance
“…Apart from the income‐related and region‐related disparity in financial protection were shown previous studies, the growing prevalence of chronic disease also contributed to high out‐of‐pocket payments (OOP) for health services and drugs. Evidence from South Korean and 15 European countries concluded that households with members suffering from chronic diseases are more likely to experience CHE than general households, even in some of the developed countries worldwide . In general, the changes over the last decade of socio‐economic disparity in financial protection in China at national level are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the income‐related and region‐related disparity in financial protection were shown previous studies, the growing prevalence of chronic disease also contributed to high out‐of‐pocket payments (OOP) for health services and drugs. Evidence from South Korean and 15 European countries concluded that households with members suffering from chronic diseases are more likely to experience CHE than general households, even in some of the developed countries worldwide . In general, the changes over the last decade of socio‐economic disparity in financial protection in China at national level are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These rates were higher than those of developed countries,but were lower than those of low-income countries. 29,30 The incidences of CHE participating in medical insurance were 3.6% higher than those of uninsured households (16.3%). In addition, families with cardiovascular disease have a much higher risk of IME than families without cardiovascular disease (7.0%) and the overall population (7.2%).It can be seen that cardiovascular disease patients' risk tolerance for health care payments is actually lower than the average in China.…”
Section: Discussionmentioning
confidence: 93%
“…Cardiovascular diseases costs are very high, so that in the European Union (EU) in 2016, the direct and indirect costs (premature death and disability) of CVDs were estimated to be about 25 and 18 billion euros, respectively (3,8). It has also increased the inequality in health care nancing by increasing OOP expenditure and catastrophic health expenditures (9). In the US, direct and indirect cost of CVDs was totally about 329.9 billion USD, and it is estimated to increase to 1.1 trillion USD in 2035 (10).…”
Section: Introductionmentioning
confidence: 99%